Swallowing pressure and pressure profiles in young healthy adults. (17th September 2013) - Matsubara, Keigo; Kumai, Yoshihiko; Samejima, Yasuhiro; Yumoto, Eiji
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To measure the swallowing pressure (SP) of normal subjects using a 2.64‐mm‐diameter high‐resolution manometry (HRM) catheter with 36 circumferential sensors. Study Design Repeated measures with subjects serving as controls. Methods Thirty healthy subjects swallowed water at different temperatures and volumes to examine the maximum SP at the velopharynx, meso‐hypopharynx, upper esophageal sphincter (UES), and cervical esophagus, and the duration of lowered pressure at the UES. Results The maximum SP at any location was unaffected by the volume of water, whereas the maximum SP at the UES and cervical esophagus was affected by the temperature. The duration of lowered SP at the UES was significantly prolonged with 10 versus 2 mL of cold water. The pressure curve in males had two peaks (at the velopharynx and UES), whereas that of females had a single peak at the UES. Conclusions Our data obtained with 2.64‐mm HRM demonstrated that as the bolus volume is increased, the duration of lowered SP at the UES is prolonged. The higher maximum SP at the velopharynx in males versus females suggests that there may be a gender difference in pressure at the velopharynx that has not been described previously. This implies that it is necessary to take gender differences into consideration when evaluating the etiology of swallowing dysfunction by examining the SP and SP curve. Moreover, the thinner catheter is less invasive and may contribute to obtaining more physiological measurements. Level of Evidence 4 Laryngoscope, 124:711–717, 2014